Особенности численного моделирования течения вязкой жидкости в каналах погружных лопастных насосов низкой и средней быстроходности - Шевченко, Наталья Григорьевна; Шудрик, Александр Леонидович; Радченко, Лариса Рудольфовна (НТУ "ХПИ", 2015)
Проведен анализ особенностей рабочего процесса и численного моделирования течения вязкой жидкости в ступени погружного центробежного насоса с коэффициентом быстроходности ns = 100. Даны рекомендации по выбору модели турбулентности и построению расчетной сетки. Выполнено трехмерное моделирование потока с помощью ANSYS CFX. Полученные интегральные характеристики насоса ЭЦНД5-80 хорошо согласуются с экспериментом. Приведена визуализация результатов расчета в проточной части ступени.

The analysis of features of working process and numerical modeling of a current of viscous liquid is carried out to steps of the submersible centrifugal pump with coefficient of rapidity of ns = 100. Recommendations about a choice of model of turbulence and creation of a settlement grid in flowing part are made. Three-dimensional modeling of a stream of liquid in the submersible centrifugal pump by means of the program ANSYS CFX complex is executed. Good coordination of settlement and experimental integrated characteristics of the pump ESP5-80 is received. Visualization of results of calculation of kinematics of a stream, distribution of speed and pressure is given in flowing part of a step. Possibilities of use of program production of ANSYS CFX are analyzed on example of calculation of multiphase liquids and the accounting of a roughness. It will allow predict characteristic of the pump when pumping real liquid during the periods of long operation with high precision.
Features of numerical modeling flow of viscous liquid in channels of submersible bladed pumps of low and average rapidity
Keywords: центробежный насос; рабочее колесо; направляющий аппарат; ступень насоса; математическая модель; модель турбулентности; интегральные характеристики; centrifugal pump; current of viscous liquid; mathematical model; turbulence model; integrated characteristics